System of Continuous Improvement for a Cooperative Organization in Southern Brazil (Research, Society and Development, 2021)
Quality management requires from organizations more than knowledge and practices about tools and more than tradition and commitment to quality. It requires a system of continuous improvement which, although it can be guided by formal instruments (standards, models), must be structured based on the application of theoretical knowledge to the reality of each organization. This study aimed to suggest a system of continuous improvement suitable to the operations of a cooperative organization in the agricultural sector, located in the south of Brazil. The exploratory and descriptive study used interviews, on-site observation and document analysis. As a result, we suggest a continuous improvement system based on the PDCA cycle (Plan, Do, Check, Act), with quality tools associated with each stage, with emphasis on the planning stage, which requires more decisions than the others. In addition, it is suggested to intensify the training of employees and review the criteria for setting goals, in order to create conditions to organically integrate a set of elements capable of effectively contributing to the continuous improvement of the studied organization's processes.